(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problem of social structure of societies of evangelic Christians-Baptists in 20-s of XX century. The author underlines that in soviet times the estimation of social structure of societies was the item of ideological speculations. On the archived materials of Zaporizhzhia neighborhood the author characterizes the social, property, sexual and age-old structure of societies, dethroning a myth about concentration of evangelic Christians-Baptists of ´exploitative layersª and ´enemies of peopleª in societies.